2014
DOI: 10.3389/fimmu.2014.00171
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Responses to Viral Infections – Opportunities for Peptide Vaccination

Abstract: An effective immune response against viral infections depends on the activation of cytotoxic T cells that can clear infection by killing virus-infected cells. Proper activation of these T cells depends on professional antigen-presenting cells, such as dendritic cells (DCs). In this review, we will discuss the potential of peptide-based vaccines for prevention and treatment of viral diseases. We will describe features of an effective response against both acute and chronic infections, such as an appropriate mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
106
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(113 citation statements)
references
References 102 publications
0
106
1
Order By: Relevance
“…For prevention of infectious diseases, the use of therapeutic or prophylactic vaccines can be a successful method for directing the immune system against specific pathogens. A peptide vaccine with greater efficacy against pathogens would bring about a major improvement in protection of the population against infection (38)(39)(40). Our previous findings that the T-cell response was an important component of naturally acquired immunity to control HTNV infection provide the foundation for the development of HTNV peptide vaccines that may combat HTNV by efficiently inducing specific T-cell immunities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For prevention of infectious diseases, the use of therapeutic or prophylactic vaccines can be a successful method for directing the immune system against specific pathogens. A peptide vaccine with greater efficacy against pathogens would bring about a major improvement in protection of the population against infection (38)(39)(40). Our previous findings that the T-cell response was an important component of naturally acquired immunity to control HTNV infection provide the foundation for the development of HTNV peptide vaccines that may combat HTNV by efficiently inducing specific T-cell immunities.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to MHC restrictions and low immunogenicity, the broad applicability of peptide vaccines for diseases may be currently limited. Several studies on various clinical applications of peptide vaccines have suggested that many potential variables, such as the type and length of peptides, the loading of one or multiple peptides on antigen-presenting cells (APCs) or the route of administration may attribute to the design efficiency of peptide vaccines (25,39,40). Selecting the right epitope is the first crucial step in the design of an effective vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adding adjuvants might induce detectable T‐cell responses in this approved vaccine. Even a combination of the Hecolin ® vaccine together with peptides encoded by ORF1 and/or ORF2/3 in combination with an adjuvant might be considered …”
Section: Discussionmentioning
confidence: 99%
“…(12) As the most powerful APC in vivo, DCs are able to uptake antigens, then process and present them to T-cells to initiate the corresponding immune response, thereby enhancing specific anti-HBV capacity and improving the patient's active immunity. (22) Here, we studied the effects of dendritic cells on HBV transgenic mice-stimulated autologous lymphocytes on in vitro HBV replication, with an emphasis on covalently closed circular DNA (cccDNA). Our goal was to evaluate changes in specific immune function after HBV infection and its relationship with HBV replication.…”
Section: Introductionmentioning
confidence: 99%